Frailty is associated with longer hospital stay and increased mortality in hospitalized older patients - Khandelwal, D.; Goel, A.; Kumar, U.; Gulati, V.; Narang, R.; Dey, A.B. (The Journal of nutrition, health & aging, 2012)
With the onset of frailty, there is often a rapid, progressive, and self-perpetuating downward spiral towards death. Frailty has enormous impact on acute hospital care and has been shown to be a more effective predictor of mortality than conventional clinical measures. Hospitalized older patients admitted in medical wards at a teaching public hospital were studied to determine the prevalence of frailty; its association with anemia, congestive heart failure, clinically active tuberculosis and cognitive impairment; as well as its impact upon short-term outcome. A total of 250 older hospitalized patients were included, and their frailty status was assessed using Fried's criteria. Of these, 83 (33.2%) patients were frail, with frailty found to be significantly associated with increasing age. A lower mean level of haemoglobin (p, 0.002), higher chance of congestive heart failure (p, <0.001), lower mean MMSE score (p, <0.001), was found in frail older patients. Frail subjects had a higher median hospital stay. There were total of 5 deaths, all among the frail group. Our study showed that almost a third of hospitalized older patients are frail, and have anemia, higher frequency of CHF, cognitive impairment, longer hospital stay and higher mortality.